2019
DOI: 10.1097/nna.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

A Leadership Opportunity

Abstract: Despite the availability of the political process, it has not been used optimally by nurses to improve negative issues facing the profession. This study indicates that nurses are generally not astute regarding the political process and are not significantly involved. Nurse leaders have an opportunity to educate and motivate nurses to be formidable participants in the political process, champion the healthcare agenda, and propound policy efforts to improve patient care and the nursing profession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Some similarities exist between elements of political astuteness as measured by the Political Astuteness Inventory (Clark, 2008;Primomo & Bjorling, 2013;VandeeWaa et al, 2019)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some similarities exist between elements of political astuteness as measured by the Political Astuteness Inventory (Clark, 2008;Primomo & Bjorling, 2013;VandeeWaa et al, 2019)…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to understand how nurses participate in health policy have been evident in the nursing literature for decades. Concepts studied vary from political participation (Hanley, 1987), to public policy involvement (Oden et al, 2000), to organized political participation (Cramer, 2002;Vandenhouten et al, 2011), to political astuteness (Primomo & Bjorling, 2013;VandeeWaa et al, 2019). As can be seen in Box 1, despite a lack of agreement about the concepts to study and terminology to address nurses' involvement in policy and advocacy, there is a growing body of literature addressing ways to conceptualize and measure nurses' health policy participation globally.…”
Section: Measuring Nurses' Health Policy Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…VandeWaa and colleagues compared the responses from 2016 to 2018 to assess the political astuteness in nurses, not specifically nursing leaders. 9,10 VandeWaa et al utilized the Political Astuteness Inventory (PAI) to gather their data and reported that the majority of nurses are not aware of the issues that are on voting ballots. 11 Liou et al 12 studied the perception of important competencies in nursing leadership; political astuteness was consistently on the bottom regardless of the nurses' leadership level.…”
Section: Background Level Of Political Astutenessmentioning
confidence: 99%
“…There is very little current literature regarding the level of political astuteness in nursing leaders. VandeWaa and colleagues compared the responses from 2016 to 2018 to assess the political astuteness in nurses, not specifically nursing leaders 9,10 . VandeWaa et al utilized the Political Astuteness Inventory (PAI) to gather their data and reported that the majority of nurses are not aware of the issues that are on voting ballots 11 .…”
Section: Introductionmentioning
confidence: 99%